Bio-linguistics : the Santa Barbara lectures - Givón, Talmy, 1936- (J. Benjamins Pub. Co., 2002)
Is human language an evolutionary adaptation? Is linguistics a natural science? These questions have bedeviled philosophers, philologists and linguists from Plato through Chomsky. Prof. Givón suggests that the answers fall naturally within an integrated study of living organisms. In this new work, Givón points out that language operates between aspects of both complex biological design and adaptive behavior. As in biology, the whole is an adaptive compromise to competing demands. Variation is the indispensable tool of learning, change and adaptation. The contrast between innateness and in.